2017
DOI: 10.1088/2399-6528/aa9c4f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mn doped CH3NH3PbBr3perovskite microrods and their collective EMP lasing

Abstract: Diluted magnetic semiconductor (DMS) nanostructures are promising platform to modulate carriers and spins for new information devices. Here we report that the high quality pure CH 3 NH 3 PbBr 3 microrods and Mn doped CH 3 NH 3 PbBr 3 microrods have been prepared by solution method and in which the exciton magnetic polarons (EMP) formed in Mn doped microrods, and a single mode lasing phenomenon from collective EMP in single microrod have been detected when excited by fs pulse laser. This finding helps to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…2D NPLs, which are highly quantum confined in the z direction, could not afford the ferromagnetism of Mn ions to exist in nanometer size. 32,33 In the present investigation, the aforementioned effect is ruled out, and there is another reason that may be held responsible for the increased lifetime in the Mn-doped CsPbBr 3 NPLs.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…2D NPLs, which are highly quantum confined in the z direction, could not afford the ferromagnetism of Mn ions to exist in nanometer size. 32,33 In the present investigation, the aforementioned effect is ruled out, and there is another reason that may be held responsible for the increased lifetime in the Mn-doped CsPbBr 3 NPLs.…”
mentioning
confidence: 70%
“…Therefore, it can be clearly concluded that the EMP formation occurs in bulk materials. 32,33 In addition, the excited state of 4 T 1 in Mn 2+ resides within the CsPbBr 3 NPL band gap; immediately after excitation of the Mn-doped CsPbBr 3 NPLs, rapid energy transfer from the host to Mn 2+ takes place within 1 ps, and there is not sufficient time for EMP formation (100 ps). 2D NPLs, which are highly quantum confined in the z direction, could not afford the ferromagnetism of Mn ions to exist in nanometer size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, microrod and nanorods of CH 3 NH 3 PbBr 3 and CH 3 NH 3 PbI 3 structures were also reported (Table S1). To gain more mechanistic insight into the conversion from FAPbX 3 to MAPbX 3 , we have done the solid-state magic angle spinning (MAS) 1 H NMR of all the compounds (Figure c,f). The characteristic CH (8.06–8.10 ppm) and NH 2 (8.76–9.04 ppm) broad peaks , of FA + are observed in FAPbX 3 , but those peaks disappear in MAPbX 3 , and the CH 3 (4.15–4.22 ppm) and NH 3 (6.67–6.88 ppm) broad peaks of MA + appear at different positions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, exciton-polariton condensates allowed for the to observation of some fascinating phenomena from superfluid excitations [20][21][22][23][24][25][26] , to solitons [27][28][29] . Several possible applications have been put forward as well, ranging from low threshold lasers 30,31 , to all-optical transistors [32][33][34] , to quantum simulation 35,36 .…”
Section: Introductionmentioning
confidence: 99%